JOB INSECURITY – CONCEPTUALIZATION OF THE NOTION AND METHODS OF MEASUREMENT - Joanna Wyrwa (Acta Scientiarum Polonorum. Oeconomia, 2019)
Increasing globalization and transformation of the modern labour market have changed the traditional employment model, introducing insecurity associated with taking up and maintaining work. Job insecurity, understood as a “perceived threat of job loss and concerns related to this threat” is an unavoidable and widespread phenomenon in today’s professional world. Job insecurity has been of great interest to researchers since the 1980s. Job insecurity is one of the emerging research directions in economic theory. The aim of the article is to try and provide an interdisciplinary conceptualization of job insecurity. The article presents different ways of understanding job insecurity and discusses the methods of its measurement. A systematic review of world literature was conducted to identify and assess the current state of knowledge in this area. The analysis of scholarly publications on job insecurity confirms the existence of a relatively small number of scientific and research studies in this field in Poland. Therefore, a cognitive gap is identified which invites a more indepth investigation of job uncertainty, in particular its integrated review and conceptual framework as well as designing the relevant measurement tool. The article is analytical and conceptual, and can be a contribution to the discussion on job insecurity and a starting point for empirical research in economic sciences.